Determination of Inhibition Activity for Arak and Cloves Against Aerobic Bacterial Isolates from Patients of Dental Caries and Gingivitis - Abdul-Rahman Jarjees Younis1; Mahmood Khalaf Saleh (Tikrit Journal of Pure Science, 2020)
One hundred and nine samples were collected from General Hospital and some outpatient dental clinics in Al-Shirqat city through the period from 10/10/2018 to 20/3/2019 to determine the bacterial species causing dental caries and gingivitis by culturing on culture media, it was diagnosed phenotypically and biochemically as well as modern methods using Vitek-2 compact system technique. The species isolated as were: Staphylococcus epidermidis (51.37%), Streptococcus mutans (19.26%), Staphylococcus aureus (12.84%), Lactobacillus acidophilus (7.33%), Escherichia coli (5.50%), Streptococcus pneumoniae (3.66%). The sensitivity of isolates was tested for fourteen antibiotics. The plant extracts were more effective than antibiotics, especially at 100 mg / ml. Not all isolates were affected by 10 mg / ml.